First record of the starfish Luidia atlantidea in the Canary Islands - Osaer, Filip (2018)
We document the first observations of Luidia atlantidea Madsen, 1950 (Luidiidae; Paxillosida, Asteroidea) along the coasts of the Canary Islands, which represents a new westward occurrence of its known range. Individuals were observed during a visual scuba diving census in the islands of Gran Canaria (northwestern and eastern coasts) and Tenerife (eastern coast). These occurrences highlight the importance of the systematic biodiversity monitoring and surveillance of the dynamic changes in the environment, whereas future research is required to reveal the underpinnings for its presence.